Non-Operative Management with Angioembolization of Grade IV and V Renal Injuries in a Hybrid Emergency Room System - So Ra Ahn; Sang Hyun Seo; Joo Hyun Lee; Chan Yong Park (Journal of Trauma and Injury)
Renal injuries occur in more than 10% of patients who sustain blunt abdominal injuries. Non-operative management (NOM) is the established treatment strategy for lowgrade (I–III) renal injuries. However, despite some evidence that NOM can be successfully applied to high-grade (IV, V) renal injuries, it remains unclear whether NOM is appropriate in such cases. The authors report two cases of high-grade renal injuries that underwent NOM after embolization in a hybrid emergency room (ER) system with a 24/7 in-house interventional radiology (IR) team. A 29-year-old male visited Wonkwang University Hospital Regional Trauma Center complaining of right abdominal pain after being hit by a rope. Computed tomography (CT) was performed 16 minutes after arrival, and the CT scan indicated a grade V right renal injury. Arterial embolization was initiated within 31 minutes of presentation. A 56-year-old male was transferred to Wonkwang University Hospital Regional Trauma Center with a complaint of right flank pain. He had initially presented to a nearby hospital after falling from a 3-m height. Thanks to the key CT images sent from the previous hospital prior to the patient’s arrival, angiography was performed within 8 minutes of the patient’s arrival and arterial embolization was completed within 25 minutes. Both patients were treated successfully through NOM with angioembolization and preserved kidneys. Hematoma in the first patient and urinoma in the second patient resolved with percutaneous catheter drainage. The authors believe that the hybrid ER system with an in-house IR team could contribute to NOM and kidney preservation even in high-grade renal injuries.